The Effect of Career Development, Compensation and Employee Retention on Employee Performance at PT Semen Indonesia Logistik - Tatiek Sulistiowati (Jurnal Indonesia Sosial Teknologi, 2024)
The purpose of study to identify the effect of career development, compensation and employee retention on employee performance at pt semen indonesia logistik. This study used quantitative methods. The analysis method used in this study is multiple linear regression analysis method. This method is used to analyze the effect of career development, financial compensation and employee status on the performance of PT Semen Indonesia Logistik employees. Based on the results of multiple linear regression analysis, it can be concluded as follows: First, compensation has a positive and significant impact on employee performance, as evidenced by the value of the regression coefficient (b1) of 0.314 with a significance value (Sig. = 0.000). Therefore, the first hypothesis is acceptable, suggesting that an increase in compensation received by employees of PT Semen Indonesia Logistik will improve their performance. Second, Career Development has a positive and significant impact on employee performance, reinforced by the regression coefficient (b2) value of 0.183 with a significance value (Sig. = 0.017).